Source apportionment, contamination levels, and spatial prediction of potentially toxic elements in selected soils of the Czech Republic - Agyeman, Prince Chapman; Ahado, Samuel Kudjo; Kingsley, John; Kebonye, Ndiye Michael; Biney, James Kobina Mensah; Borůvka, Luboš; Vasat, Radim; Kocarek, Martin (Environmental geochemistry and health, 2021)
The sustenance of humans and livestock depends on the protection of the soil. Consequently, the pollution of the soil with potentially toxic elements (PTEs) is of great concern to humanity. The objective of this study is to investigate the source apportionment, concentration levels and spatial distribution of PTEs in selected soils in Frýdek-Místek District of the Czech Republic. The total number of soil samples was 70 (topsoil 49 and 21 subsoils) and was analysed using a portable XRF machine. Contamination factor and the pollution index load were used for the assessment and interpreting the pollution and distribution of PTEs in the soils. The inverse distance weighting was used for the spatial evaluation of the PTEs. The results of the analysis showed that the area is composed of low-to-high pollution site. PTEs displayed spatial variation patterns. The average PTE concentration decreases in this Fe > Ti > Ba > Zr > Rb > Sr > Cr > Y>Cu > Ni > Th order for the topsoil and also decreases in this Fe > Ti > Zr > Ba > Rb > Sr > Cr > Y > Cu > Ni > and Th order for the subsoil. These PTEs Cr, Ni, Cu, Rb, Y, Zr, Ba, Th, and Fe were far above the baseline European average value and the World average value level, respectively. The source apportionment showed the dominance of Cr, Ni, Rb, Ti, Th, Zr, Cu, Fe in the topsoil, while the subsoil was dominated by all the PTEs (factor 1 to 6) except Ba. The study concludes that indiscriminate human activities have an enormous effect on soil pollution.
Keywords: Spatial Analysis; Risk Assessment; Česká republika; látky znečišťující půdu; lidé; hodnocení rizik; znečištění životního prostředí; Environmental Pollution; Soil; půda; prostorová analýza; těžké kovy; Metals, Heavy; Czech Republic; Soil Pollutants; Environmental Monitoring; monitorování životního prostředí; Humans